Perencanaan Dakwah Nahdlatul Ulama Cabang Asahan dalam Membina Kerukunan Umat Beragama di Kota Kisaran - Agus Kurniawan; Soiman Soiman (Dinasti Research, 2024)
This research is to find out in depth about the preaching of Nahdlatul Ulama Asahan Branch in fostering religious harmony in Kisaran City. Aims to identify the management implementation carried out by PCNU Asahan in carrying out each activity with good and correct planning. The research used field research with a qualitative approach which aims to analyze the preaching planning of Nahdlatul Ulama Asahan Branch in fostering religious harmony in Kisaran City, Asahan Regency. The results of this research carried out each activity by activity carried out by the NU Asahan Branch, starting with planning at the beginning by preparing everything needed for the activity. PCNU provides comfort and build a harmonious environment so that there is no discrimination and there is no divion between people in society. And provide positive values for the people of the city kisaran.